OPTIMAL PORTFOLIO FORMATION ANALYSIS USING THE SINGLE INDEX MODEL DURING THE COVID-19 PANDEMIC: A Study on The LQ 45 Index on the Indonesian Stock Exchange (IDX) - Rafiana A. S., Andi Besse; Maulana, M. Ikhwan; Anwar; Burhanuddin; Nurman (Transpublika Publisher, 2023)
This study aims to determine the optimal portfolio formation using the single index model method on LQ 45 Index stocks for the period from March 2020 to December 2021. The population in this study consists of all company shares included in the LQ 45 Index during the specified period, totaling 45 stocks. A sample of 36 companies was selected using a nonprobability sampling technique with a purposive sampling method. Data collection was carried out using documentation techniques, primarily focusing on collecting closing stock price data. The data analysis process involved collecting the closing stock price data and utilizing the single index model method to identify an optimal portfolio. The results of this study indicate that 18 company shares were included in the optimal portfolio. These companies are ADRO (7.46%), AKRA (14.51%), ANTM (7.97%), ASII (4.42%), BBNI (3.3%), BBTN (1.8%), BMRI (4.55%), CPIN (1.45%), ERAA (11.14%), EXCL (3.19%), INCO (8.55%), INKP (3.98%), ITMG (5.08%), JPFA (4.86%), JSMR (3.37%), KLBF (8.3%), TKIM (1.85%), and TOWR (4.23%). The expected return for the portfolio is 4.38% per month, with a portfolio risk borne by investors of 0.29% per month. The study suggests that constructing a portfolio with the identified stocks can yield favorable returns. However, it is crucial to regularly reassess and adjust portfolios due to changing market conditions and individual risk preferences. The implications highlight the benefits of using the single index model for portfolio formation. By considering the relationship between individual stocks and the LQ 45 Index, investors can make informed decisions to maximize returns while managing risk. These specific stocks can serve as a starting point for further research in portfolio management.